Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/casp.2516
|View full text |Cite
|
Sign up to set email alerts
|

Prosociality and hoarding amid the COVID‐19 pandemic: A tale of four countries

Abstract: The COVID-19 pandemic is an unprecedented public health crisis that poses a challenge to humanity. Drawing on the stress and coping literature, we argue that people around the world alleviate their anxiety and stress induced by the pandemic through both prosocial and 'self-interested' hoarding behaviours. This cross-cultural survey study examined the pushing (threat perception) and pulling (moral identity) factors that predicted prosocial acts and hoarding, and subsequently psychological well-being. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Nonetheless, studies developed in the context of the COVID-19 pandemic have demonstrated that PsB can be manifested in different ways, depending on the cultural context (Tse et al, 2021). This is of great relevance for the context of this study (i.e., the urban population in Colombia) because previous studies on SWL concluded that research participants experienced satisfaction despite the financial crisis created by the COVID-19 pandemic (Cudris-Torres et al, 2021).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nonetheless, studies developed in the context of the COVID-19 pandemic have demonstrated that PsB can be manifested in different ways, depending on the cultural context (Tse et al, 2021). This is of great relevance for the context of this study (i.e., the urban population in Colombia) because previous studies on SWL concluded that research participants experienced satisfaction despite the financial crisis created by the COVID-19 pandemic (Cudris-Torres et al, 2021).…”
Section: Introductionmentioning
confidence: 81%
“…The COVID-19 pandemic has severely impacted societies (Alkhamshi et al, 2021;Coccia, 2021), businesses (Singh et al, 2021), and personal finances (Cudris-Torres et al, 2021). This unprecedented situation has restricted productivity in many sectors, negatively impacting economies (Cudris-Torres et al, 2021) and posing challenges to people everywhere (Tse et al, 2021). During times of crises such as the COVID-19 pandemic as well as natural disasters like earthquakes and hurricanes (Maki et al, 2019), prosociality or prosocial behavior (PsB) has been of interest to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the participants of this Taiwanese study were proud to be involved in epidemic control. A possible reason could be that different people have different interpretations of “heroes” or “honor” [ 42 ]. The present study proved that acknowledgment and acceptance by the public toward healthcare workers is one of the important supports for the emergency department nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Such problems are of particular importance amid the pandemic, as COVID-19 is a highly contagious disease and facemask use serves as an effective measure for decreasing the likelihood of contracting the novel virus (e.g., Eikenberry et al, 2020 ; Wang et al, 2021 ). Individuals of higher SES are more capable of accruing personal resources and social capital to prevent viral contraction, especially at difficult times when pandemic hoarding and inflated prices of personal protective equipment are common (e.g., Cheng et al, 2021b ; Tse et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%